Development of the KAI Model (Collaborative, Adaptive, Individual) to Improve Elementary School Students’ Literacy - Supraptini, Caecillia; Putra, Chandra Anugrah; Hendri, Hendri (Reflection Journal, 2026)
This study developed the KAI Model, an instructional innovation integrating collaborative, adaptive, and individual learning to improve literacy instruction at SD Negeri Balai Riam. The study was motivated by classroom conditions in which literacy learning remained largely teacher-centered, learning strategies were limited, and students showed varied reading abilities. Using a Research and Development design with the 4D model consisting of define, design, develop, and disseminate stages, this study produced a literacy learning model, teaching module, student worksheets, and assessment instruments for Grade IV Indonesian language learning. Data were collected through observation, interviews, expert validation, teacher and student responses, and pretest-posttest assessment. The results show that the KAI Model was highly feasible, with expert validation scores of 90% for media feasibility, 100% for material feasibility, 83.3% for language feasibility, and an overall average of 91.1%. Classroom implementation indicated that the model could be applied systematically through orientation, collaborative text discussion, adaptive task differentiation, individual literacy work, and reflection. The model also received positive responses from teachers and students because it encouraged active participation, peer discussion, motivation, and independent learning. Its effectiveness was demonstrated by an increase in students’ average literacy score from 55.7 in the pretest to 77.2 in the posttest, with a moderate N-Gain of approximately 0.49. These findings indicate that the KAI Model is valid, practical, and effective as a contextual literacy learning model for elementary schools.